Groundwater Balance Approach as Basic Planning for Sustainability of Settlement Development - Deddy Sugianto; Arief Rachmansyah; Rita Parmawati (The Indonesian Green Technology Journal, 2019)
Demands for environmental protection, especially water resources and in development planning, have shown an increase in recent years. However, the reference for protection of water resources has always been based on the level of pollution or changes in water quality. This paper discusses groundwater balance as an approach for housing development planning. This approach assumes that all water needs for residents in a settlement area and their activities are met from groundwater, and the used groundwater must be replaced by water absorption into the soil in the area. For this reason, comprehensive rainwater management is needed. The potential for rainwater in residential areas requires greater management efforts; in addition to controlling the runoff that occurs, the use of clean water is also necessary. The results of runoff analysis for housing in downstream and upstream areas showed a potential for runoff of approximately 105-115% from before the construction of housing until after it has been inhabited. Rainwater management by using infiltration wells as large as 0.82 m3/m2 and water balance of 13.3% is less effective in downstream areas with shallow groundwater levels, but more effective in reservoirs and for seepage of runoff water using a catchment pool of 28.26% or 1.74 m3/m2.Meanwhile, for housing in upstream areas with a low permeability coefficient, the infiltration pond is less effective for water infiltration into the soil by 0.032 m3/m2 or 0.0054%, with a higher level of groundwater than in the downstream housing areas, which can use more effective infiltration wells. Overall, the management of rainwater for clean water and drinking water has sufficient discharge and the quality of the pH of rainwater from the roofs of houses is still feasible, between 6.6 and 7.8. The perspective of people on the use of rainwater as clean water and drinking water is quite positive, at approximately 59-61%.Keywords: Groundwater balance, rainwater harvest, sustainable settlement